2011
DOI: 10.1007/s00432-011-1124-8
|View full text |Cite
|
Sign up to set email alerts
|

The functional MDM2 T309G genetic variant but not P53 Arg72Pro polymorphism is associated with risk of sarcomas: a meta-analysis

Abstract: These results suggest that the functional MDM2 T309G genetic variant may play a more important role in carcinogenesis of sarcoma.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

3
14
0

Year Published

2012
2012
2015
2015

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 20 publications
(17 citation statements)
references
References 47 publications
3
14
0
Order By: Relevance
“…These findings are consistent with most of the published studies reporting the relationship of SNP rs2279744 and risk of sarcoma and the experimental data as previously detailed. An early metaanalysis of four independent studies showed a 34 % elevated risk to develop sarcoma ascribed to the TG and GG genotypes, a discovery similar to that revealed in the current study [30]. Nevertheless, Cai et al failed to include a subsequently published study and assumed one comparison model (T/T vs T/G+G/G) only, and it is the relatively smaller sample and the effect size estimation for a single model may likely lead consequently to an underestimated association.…”
Section: Discussionsupporting
confidence: 87%
“…These findings are consistent with most of the published studies reporting the relationship of SNP rs2279744 and risk of sarcoma and the experimental data as previously detailed. An early metaanalysis of four independent studies showed a 34 % elevated risk to develop sarcoma ascribed to the TG and GG genotypes, a discovery similar to that revealed in the current study [30]. Nevertheless, Cai et al failed to include a subsequently published study and assumed one comparison model (T/T vs T/G+G/G) only, and it is the relatively smaller sample and the effect size estimation for a single model may likely lead consequently to an underestimated association.…”
Section: Discussionsupporting
confidence: 87%
“…Ma showed a significant relationship between the MDM2 SNP309T>G and liver cancer risk, and the G allele contributed to increased risk in a graded, dose-dependent manner (Ma et al, 2012), and Cai indicated the functional genetic variant may play an important role in sarcoma carcinogenesis (Cai et al, 2012); however, Chen reported the polymorphism is a protective factor against prostate cancer risk in Europeans (Chen et al, 2012) and Liu suggested the G allele probably acted as a protective factor in head and neck squamous cell carcinomas in Caucasians (Liu et al, 2011). Similarly, several publications focused on the association between gastric cancer and the polymorphism, nevertheless, no agreement was achieved.…”
Section: Introductionmentioning
confidence: 99%
“…Our data demonstrate that the allele-A and genotype-AA of the MDM2 c.346G > A genetic variant are risk factors for the susceptibility to osteosarcoma in the Chinese Han population. The MDM2 c.346G > A genetic variant is a nonsynonymous mutation, and might impact the expression and function of the MDM2 protein, which is potentially associated with the risk of osteosarcoma (Wunder et al, 1999;Toffoli et al, 2009;Mejia-Guerrero et al, 2010;Mirabello et al, 2011;Cai and Yang, 2012;Naumov et al, 2012;He et al, 2013). Up to now, this is the first report with regard to a potential association between MDM2 c.346G > A and the risk of osteosarcoma.…”
Section: Discussionmentioning
confidence: 78%
“…It has been proposed that genetic factors play key roles in the risk of osteosarcoma, and influence the prognosis of osteosarcoma patients (Fuchs et al, 2001;Savage et al, 2007;Salinas-Souza et al, 2010;Caronia et al, 2011;Liu et al, 2011;Wang et al, 2011;Liu et al, 2012;He et al, 2013;He et al, 2014). Previous studies suggest that the MDM2 gene is one of the most important candidate genes for influencing the development of osteosarcoma (Wunder et al, 1999;Toffoli et al, 2009;Mejia-Guerrero et al, 2010;Mirabello et al, 2011;Cai and Yang, 2012;Naumov et al, 2012;He et al, 2013). The single-nucleotide polymorphisms (SNPs) of the MDM2 gene may affect the expression and function of the MDM2 protein, thus influencing the risk of osteosarcoma.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation